Evaluation of Bunsen Reaction Kinetics in Iodine-sulfur Thermochemical Process for Hydrogen Production - Nafees Ahmed Vakil; Shriniwas A Rao (Computational and Experimental Research in Materials and Renewable Energy, 2024)
There are many thermochemical processes; one of the potential processes is iodine-sulfur (IS) thermochemical process which involves three reaction steps. Bunsen reaction is the first reaction. Kinetic rate data of Bunsen reaction is essential for design and scale up of I-S process. Experiments have been carried out in stirred glass reactor to determine kinetic rate data for Bunsen reaction. The aim of the work is to evaluate intrinsic kinetic rate constant of Bunsen reaction. Mass transfer coefficient is evaluated experimentally for water-sulfur dioxide system. Stirring speed is varied up to 360rpm to obtain a regime in which mass transfer is independent of absorption rate. Mass transfer coefficients are evaluated in the range of 8.7×10-6 m/s to 1.5×10-5 m/s at different stirring speeds. Mass transfer coefficients obtained experimentally. These coefficients are compared with published literature and found to be in good agreement. Bunsen reaction has been carried out in a stirred glass reactor and obtained reaction kinetic rate constant as 1.8 Second-1. Hatta number and Infinite enhancement factors are calculated from the experimentally obtained kinetic rate constant and mass transfer coefficient and found to be 3.6 and 18 respectively. From the calculated values of Hatta number and Infinite enhancement factors, the regime of chemical reaction is found to be in the fast pseudo first order reaction regime. Keywords: Hydrogen production, iodine-sulfur process, Bunsen reaction, stirred glass reactor, reaction kinetics